Formulation and Evaluation of N-Hexane Fraction of Libo Fruit based Emulgel for Sunscreen - Yuni Dwi Anjarwati; Lisna Meylina; Rolan Rusli (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2023)
Libo fruit (Ficus variegata Blume) has activity as a sunscreen. Topical form of certain pharmaceuticals can be used to protect the skin from sun exposure. This study aims to determine the best gel-emulsion formula from the libo’s N-Hexane fraction, its stability, and its sunscreen activity. The formula was consist gelling agents variations type and concentration, i.e. carbopol 940 and hydroxypropyl methylcellulose (HPMC). The best formula were chosen based on physicochemical characteristics. the freeze-thaw test deployed to check the stability, and the sunscreen activity was tested using UV-Vis spectrophotometry. The results showed that the best formula was formula 1 with carbopol 940 (1%), there were no changes in physicochemical characteristics during the stability test, and experienced a decrease in sunscreen activity after the stability test.